Linguistic borrowing between Arabic and foreign languages: Vocabulary of Arabic and Turkish language as an example - Benyounes, Chahrazed (Journal of Human Sciences, 2020)
The linguistic borrowing is a common phenomenon in the languages as long as it represents one of the most important ways by which the vocabulary background develops; because not every language can develop without external borrow from other languages. The Arabic language is one of these languages that strengthen its communicative, cognitive, cultural and functional abilities in the life’s fields, imposed by the interaction circumstances of the international civilizations and cultures. By this research, we seek to reveal this linguistic interference through the approach of two languages that have a friction with the Arabic language that are the Turkish and English language, in order to respond on the following question: what are the points of influence and impact between the Turkish and the English language? Thus, at what extend the vocabulary communication realized between these three languages?